1994
DOI: 10.1002/bjs.1800810420
|View full text |Cite
|
Sign up to set email alerts
|

Suction versus siphon drainage after axillary surgery for breast cancer: A prospective randomized trial

Abstract: ReferencesClosed suction drainage is beneficial in reducing the incidence of axillary seroma following breast surgery'-3. The incidence of postoperative seroma formation is less when the volume drained is under 30 ml per 24 h but to achieve this4 drains occasionally need to remain in situ for more than 10 days. Suction drainage may encourage continued lymphatic flow by virtue of a negative pressure effect. The present prospective study examined this hypothesis by comparing the duration and volume of drainage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Suction drain is known to obliterate the dead space left after breast surgery for cancer thereby preventing accumulation of seroma 72–77,85,90 . However, the incidence of seroma formation has been found to be higher when suction drains were used compared with passive drains, 77,78 whereas some other investigators reported no significant difference correlating to the rate of seroma between the two types of drains 79,85 . In contrast, the incidence of seroma was unacceptably high when suction drains were not used in a study by Kopelman et al 90…”
Section: Prevention and Reduction Of Seroma Formationmentioning
confidence: 98%
See 2 more Smart Citations
“…Suction drain is known to obliterate the dead space left after breast surgery for cancer thereby preventing accumulation of seroma 72–77,85,90 . However, the incidence of seroma formation has been found to be higher when suction drains were used compared with passive drains, 77,78 whereas some other investigators reported no significant difference correlating to the rate of seroma between the two types of drains 79,85 . In contrast, the incidence of seroma was unacceptably high when suction drains were not used in a study by Kopelman et al 90…”
Section: Prevention and Reduction Of Seroma Formationmentioning
confidence: 98%
“…The influence of negative pressure causing skin flap apposition to the chest wall may facilitate wound healing, reduce the incidence of wound infection, wound dehiscence or flap necrosis and prevent seroma formation 44,75,76 . There are, however, controversies correlating to the optimal suction pressure, number of drains, duration of drainage or in fact whether the drain should be used at all following breast cancer surgery 20,74,76–80 …”
Section: Prevention and Reduction Of Seroma Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Bourke et al [77] found no difference between using closed suction wound drainage and corrugated wound drainage in 51 patients who underwent simple mastectomy [78]. In a study by Whitfield and Rainsbury [79], no significant difference was observed between suction and closed siphon drainage on the formation of seroma. The choice of the number of drain tubes used has been studied.…”
Section: Drainsmentioning
confidence: 99%
“…Il permet en outre d'augmenter la liberté de mouvement et de diminuer l'inconfort des patientes opérées [42,43]. Il est devenu un standard de la prise en charge postopératoire du CA [44], même si aujourd'hui encore, son efficacité sur la diminution de la formation des séromes est discutée [45,46]. L'intensité de l'aspiration ne paraît pas non plus avoir d'incidence sur la formation de séromes.…”
Section: Prévention Postopératoire De L'apparition Des Séromesunclassified